#TITLE_ALTERNATIVE# - ADHI SRI SAKSONO (NIM:12908022); Pembimbing : Ivonne M. Radjawane M.Si, Ph.D, WAHYU
Analysis of surface current data have been done to observe surface current pattern upon North of Papua in 2012. It uses Current Meter data by TAO/TRITON (Tropical Atmosphere Ocean/Triangle Trans-Ocean Buoy Network) program from periods of January 1st 2012 to Desember 31st 2012 in 5 different buoys. The results show that the direction of surface current of North of Papua varies respected to its latitude. Serface current moves westward at 2oN during Northeast Monsoon with maximum speed 22 cm/s in January, as part of South Equatorial Current which forced its position northward through equator. This current turns eastward in June dominated by strong North Equatorial Counter Current during Southwest Monsoon. As the part of weak North Equatorial Counter Current, surface current moves eastward at 5o during Northeast Monsoon with averaged speed 29,6 cm/s in January. Contrary to another pattern told above ,which changes direction due to its monsson, surface current at 8oN constantly moves westward along 2012. This region is the southest part of North Equatoria Current. It reachs its maximum in January during boreal winter (Northeast Monsoon) with maximum speed 35,6 cm/s. As shown on its correlations between surface winds and surface current, wind affects strongly the zonal component of the current. It was caused by the position of observing point happens in the zone of strong Trade Wind. Wind plays role in changing the magnitude of flows at 8oN. At 2oN and 5oN, surface wind plays role in changin the direction of flows.